Spatial distribution of non-point source pollution from total nitrogen and total phosphorous in the African city of Mwanza (Tanzania) - Zong, Yunlong; Chen, Sophia Shuang; Kattel, Giri Raj; Guo, Zheng (Frontiers in Environmental Science, 2023)
Rapid urbanization has caused widespread environmental pollution in Africa restricting sustainable development program. Non-point source pollution is increasingly becoming one of major threats to many African cities. Here in this study, we evaluated non-point source pollution mainly based on nitrogen and phosphorus at the spatial scale of Mwanza city (Tanzania) using locally available multi-source surface data. We estimated spatial distribution of total nitrogen (TN) and total phosphorus (TP) loads at the scale of 1 square kilometer grid and came with the following conclusions: ① In year of 2020, the TN load of 2.41◊105 kg, and TP load of 4.00◊104 kg were recorded, of which 90.38 % TN and 87.23 % TP were from the informal settlements alone. The identified built-up area of the city was 28.9 km², accounting for 6.8% of the total area, and the area of informal settlements was 56.9 km2, accounted for 13.4% of the total area. ② The average load intensities of TN and TP in Mwanza city were 6.90 kg·ha-1·yr-1 and 1.14 kg·ha-1·yr-1, respectively, which was reasonably slightly higher than the average TN and TP loads in Lake Victoria basin in consistency with the high population density in Mwanza city area. ③ The TN and TP pollution loads were relatively concentrated in the inner urban area including the lower Mirongo river basin, the eastern side of the Nyamagana Peninsula and the lakeside area extending north and south from the peninsula, and gradually decreased toward the outskirt. It is proposed that thus identified riparian areas are preferred for the potentially key construction zones for pollution treatment facilities as well as the urban renewal pilots for restraining the widespread informal settlements.